2003
DOI: 10.13031/2013.13960
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inverse Estimation of Soil Hydraulic and Solute Transport Parameters From Transient Field Experiments: Homogeneous Soil

Abstract: ABSTRACT. Inverse estimation of unsaturated soil hydraulic and solute transport properties has thus far been limited mostly to analyses of one-dimensional experiments in the laboratoryshort distances (Biggar and Nielsen, 1976;Bresler et al., 1984), thus making it difficult to assign values that are applicable at the field scale.A wide range of models exists for simulating water flow and solute transport in the vadose zone. Addiscott and Wagenet (1985) gave a review of one-dimensional (1-D) transport models. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 43 publications
6
52
0
4
Order By: Relevance
“…2), so by assuming θ r as a constant value (ie in scenarios 2, 6, and 10), the estimation of the parameters was improved (Table 1). This finding is in line with other studies stating that sensitivity to the pore-connectivity parameter (l) is the lowest (Abbasi et al, 2003). Among the Mualemvan Genuchten hydraulic parameters, as mentioned by Ritter et al (2004), θ s has a clear physical meaning and can be measured directly.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2), so by assuming θ r as a constant value (ie in scenarios 2, 6, and 10), the estimation of the parameters was improved (Table 1). This finding is in line with other studies stating that sensitivity to the pore-connectivity parameter (l) is the lowest (Abbasi et al, 2003). Among the Mualemvan Genuchten hydraulic parameters, as mentioned by Ritter et al (2004), θ s has a clear physical meaning and can be measured directly.…”
Section: Discussionsupporting
confidence: 91%
“…It is commonly reported that some additional information is needed to obtain unique solutions for a large number of parameters. Such additional information could include water contents and/or pressure heads (Šimůnek and van Genuchten, 1996), solute concentrations (Abbasi et al, 2003), or temperatures (Nakhaei and Šimůnek, 2014) measured at a certain depth in the soil profile. However, little is known about the effect of including additional data as a predictor on the efficiency and uniqueness of inverse modelling of double-ring infiltrometer data.…”
Section: Introductionmentioning
confidence: 99%
“…Water contents, infiltration rates, and resident solute concentrations were used in the objective function. The similarity of the inverse 2D MIM and SPM results led to the conclusion that equilibrium transport prevailed at this field site (Abbasi et al, 2003). Regarding this conclusion one must caution that the spatial resolution of concentration data sampled at discrete positions is usually insufficient to detect PF (e.g., Kasteel et al, 2005).…”
Section: D Two-region Approachesmentioning
confidence: 61%
“…Modified HYDRUS-2D model was used in several studies comparing 2D-approaches based on SPM, MIM, or DPM for simulating PNE tracer transport in agricultural fields (e.g., Abbasi et al, 2003Abbasi et al, , 2004Köhne and Gerke, 2005;Haws et al, 2005;Köhne et al, 2006b). Abbasi et al (2003) compared the 2D MIM and SPM using inverse simulations of water flow and tracer movement at a sandy loam field plot with furrows (3 m × 3 m) in Phoenix, Arizona.…”
Section: D Two-region Approachesmentioning
confidence: 99%
See 1 more Smart Citation